Induction of Anti-Chlamydial Mucosal Immunity by Transcutaneous Immunization is Enhanced by Topical Application of GM-CSF - Hickey, Danica K.; Bao, Shisan; Ikeda, Luke T.; Carey, Alison J.; Beagley, Kenneth W. (Current Molecular Medicine, 2005)
Transcutaneous immunization (TCI) involves the direct application of antigen plus adjuvant to skin, taking advantage of the large numbers of Langerhans cells and other resident skin dendritic cells, that process antigen then migrate to draining lymph nodes where immune responses are initiated. We have used this form of immunization to protect mice against genital tract and respiratory tract chlamydial infection. Protection was associated with local antibody responses in the vagina, uterus and lung as well as strong Th1 responses in the lymph nodes draining the reproductive tract and lungs respectively. In this study we show that topical application of GM-CSF to skin enhances the numbers and activation status of epidermal dendritic cells. Topical application of GM-CSF also increased the immune responses elicited by TCI. GM-CSF supplementation greatly increased cytokine (IFNγ and IL-4) gene expression in lymph node and splenic cells compared to cells from animals immunized without GM-CSF. IgG responses in serum, uterine lavage and bronchoalveolar lavage and IgA responses in vaginal lavage were also increased by topical application of GM-CSF. The studies show that TCI induces protection against genital and respiratory tract chlamydial infections and that topical application of cytokines such as GM-CSF can enhance TCI-induced antibody and cell-mediated immunity.
Keywords: systemic immunity